2023
DOI: 10.3389/fphar.2023.1154167
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for heart failure with preserved ejection fraction: clinical evidence and potential mechanisms

Abstract: Heart failure with preserved ejection fraction accounts for a large proportion of heart failure, and it is closely related to a high hospitalization rate and high mortality rate of cardiovascular disease. Although the methods and means of modern medical treatment of HFpEF are becoming increasingly abundant, they still cannot fully meet the clinical needs of HFpEF patients. Traditional Chinese medicine is an important complementary strategy for the treatment of diseases in modern medicine, and it has been widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Another study in which elderly patients were included was carried out in China, where lower concentrations of VD were correlated with an enhanced risk of HFpEF. The findings of this study signified that VDD may be an important risk determinant regarding HFpEF [122]. The exact mechanisms through which VDD could play a part in HFpEF development are not fully understood.…”
Section: Heart Failure With Preserved Ejection Fraction (Hfpef)mentioning
confidence: 77%
“…Another study in which elderly patients were included was carried out in China, where lower concentrations of VD were correlated with an enhanced risk of HFpEF. The findings of this study signified that VDD may be an important risk determinant regarding HFpEF [122]. The exact mechanisms through which VDD could play a part in HFpEF development are not fully understood.…”
Section: Heart Failure With Preserved Ejection Fraction (Hfpef)mentioning
confidence: 77%
“…HFpEF is associated with substantial morbidity and mortality, and modern medicine offers less effective treatment ( 83 ). Various CTPMs have shown good efficacy in the context of HFpEF, but the similarities and differences in their functionality are not clear ( 84 ). Therefore, selecting the most suitable CTPMs for patients has become an important clinical problem that needs to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have reported that various TCM preparations, including decoctions, powders, tablets, capsules, and others, have shown positive therapeutic effects on HFpEF ( 84 , 86 ). However, these reviews have described these effects without quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation